Pengembangan Media Pembelajaraan Sosial Emosional (PSE) Berbentuk Doratoon pada Kelas V SD Negeri 27 Salafen Kabupaten Raja Ampat - Yubelina Oktofina Hay; Firman Firman; Dian Nitari Ribanor Sabarudin (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
SD Negeri 27 Salafen in Raja Ampat has not yet implemented varied video learning media. This study aims to develop a valid, practical, and effective Doratoon-based video learning media for use in the learning process. The research method used is Research and Development (R&D), adopting the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data were collected through observation, interviews, documentation, and other data collection instruments. The subjects of this study were 24 students from grade V of SD Negeri 27 Raja Ampat. Based on the results, the development of Doratoon-based video learning media showed very positive results. Validation was conducted by two validators, namely a material expert and a media expert. The material expert’s validation resulted in an average percentage of 97%, while the media expert achieved an average percentage of 86%, both falling into the "Very Valid" category. This indicates that the developed media met very good criteria for use in the learning process. The practicality of the learning media was measured using a respondent questionnaire, which showed an average percentage of 95.1%, classified as "Very Practical." Additionally, the effectiveness of the learning media was assessed using another respondent questionnaire, resulting in an average percentage of 95.7%, which is classified as "Very Effective." Based on the trial results from grade V students, the average score obtained was 87%, which is categorized as "Very Good." Based on the results of this study, it can be concluded that the development of Doratoon-based video learning media is valid, practical, and effective for use in the learning process at SD Negeri 27 Salafen. This media is expected to serve as a solution to improve the quality of learning, making it more interactive and engaging, and can be used as an innovative alternative for learning in schools, especially in remote areas like Raja Ampat. This study also provides an important contribution to developing digital-based learning technology in such regions.